Synergizing Design Thinking and Lean Enablers for Adaptive Product Innovation in Servitized Manufacturing - Noviany, Henny; Soderi, Ahmad (Novatio : Journal of Management Technology and Innovation, 2025)
The increasing shift toward servitization in manufacturing necessitates adaptive innovation models that blend customer-centric and process-efficient methodologies. This study investigates how the strategic integration of Design Thinking (DT) and Lean Enablers influences adaptive New Product Development (NPD) capabilities in manufacturing firms undergoing servitization. A mixed-methods approach was employed, combining survey data from 100–150 manufacturing firms with qualitative interviews. Key variables DT practices, Lean Enabler adoption, and adaptive NPD performance were operationalized using validated instruments. Data analysis involved regression modeling and structural equation modeling to explore mediation effects. Findings reveal that the combined adoption of DT and Lean practices leads to significant improvements in NPD performance metrics, including reduced time-to-market, lower post-launch defect rates, higher customer satisfaction (NPS), and greater readiness for servitization. Lean Enablers such as Obeya, cadence-based design reviews, and knowledge reuse were found to mediate the relationship between DT and NPD adaptability, enhancing both learning and operational efficiency. Organizational culture, leadership commitment, and cross-functional collaboration were identified as critical enablers of successful DT–Lean integration. This research offers a robust empirical and conceptual framework for integrating DT and Lean in manufacturing contexts. It contributes to the literature by validating measurement instruments and demonstrating their predictive value for adaptive innovation performance. The findings are especially relevant for firms aiming to enhance strategic agility and sustain competitive advantage in rapidly evolving markets.